2018
DOI: 10.2337/dc17-1387
|View full text |Cite
|
Sign up to set email alerts
|

Islet Interleukin-1β Immunoreactivity Is an Early Feature of Cystic Fibrosis That May Contribute to β-Cell Failure

Abstract: These findings reveal novel molecular pathways and therapeutic targets underlying islet pathology in CF subjects and may be important in developing new approaches to treat CFRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 40 publications
3
67
3
1
Order By: Relevance
“…Similarly, the fraction of somatostatin-positive δ-cells is increased in humans with CF (Abdul- Karim et al 1986, Soejima & Landing 1986, Lohr et al 1989, Bogdani et al 2017, with two other studies showing the same trend (Hart et al 2018, Hull et al 2018. PP cell area has also been shown to be increased in subjects with CF vs non-CF controls (Lohr et al 1989, Hull et al 2018. A significant decrease in PP cells between CF subjects with and without diabetes was reported in one study (Hull et al 2018) with no difference being observed in another (Iannucci et al 1984).…”
Section: Islet Pathology In Cystic Fibrosismentioning
confidence: 90%
See 4 more Smart Citations
“…Similarly, the fraction of somatostatin-positive δ-cells is increased in humans with CF (Abdul- Karim et al 1986, Soejima & Landing 1986, Lohr et al 1989, Bogdani et al 2017, with two other studies showing the same trend (Hart et al 2018, Hull et al 2018. PP cell area has also been shown to be increased in subjects with CF vs non-CF controls (Lohr et al 1989, Hull et al 2018. A significant decrease in PP cells between CF subjects with and without diabetes was reported in one study (Hull et al 2018) with no difference being observed in another (Iannucci et al 1984).…”
Section: Islet Pathology In Cystic Fibrosismentioning
confidence: 90%
“…In CF subjects with diabetes, studies demonstrating β-cell loss (relative to islet area) are relatively small (n ≤ 8 in at least one group) but consistent, reporting a decrease of ~25-30% (Iannucci et al 1984, Soejima & Landing 1986, Bogdani et al 2017. Interestingly, two larger studies (n = 12-18 subjects per group) failed to find significant loss in β-cell area when quantified per islet area (Couce et al 1996, Hull et al 2018 or per pancreas area (Hull et al 2018). Taken together, the literature is somewhat mixed but shows that loss of β cells may be a feature of CF both with and without diabetes.…”
Section: Islet Pathology In Cystic Fibrosismentioning
confidence: 99%
See 3 more Smart Citations